Odpowiedzi

2009-12-17T17:51:20+01:00
(x+3y)^-9y^ =x^+6xy+9y^-9y^ = x^+6xy

(b+3)^-(b-3)^ =b^+6b+9 -(b^-6b+9) = b^+6b+9-b^+6b-9=12b

2(3+b)^-12b =2(9+6b+b^)-12b=18+12b+2b^-12b=18+2b^

(3x-2)^+2(x+3)^=9x^-12x+4+2(x^+6x+9)=9x^-12x+4+2x^+12x+18=
=22+11x^2
2009-12-17T17:55:50+01:00
A)
(x+3y)^-9y^= x^+6xy+9y^-9y^= x^+ 6xy
b)
(b+3)^-(b-3)^ =b^+6b+9-(b^-6b+9) = b^+6b+9-b^+6b-9 = 12b
c)
2(3+b)^-12b = 2(9+6b+b^)-12b = 18+12b+2b^-12b = 2b^+18
d)
(3x-2)^+2(x+3)^= (9x^-12x+4)+2(x^+6x+9) = 9x^-12x+4+2x^+12x+18 = 11x^+22